2021
DOI: 10.25134/ijete.v2i2.4906
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Continuous Assessment Learning Activities (Cala) by the Ministry of Primary and Secondary Education in Nyanga District, Zimbabwe

Abstract: The study sought to determine the effectiveness of the implementation of Continuous Assessment Learning Activities (CALA) by the Ministry of Primary and Secondary Education in Nyanga, Zimbabwe. The researchers were motivated to carry out the research due to the endless outcry by students who are finding CALA difficult to execute and teachers who are also finding it difficult to guide the students. The initiative was introduced by the Ministry of Primary and Secondary Education arguably without proper planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Skilled workers would fully understand the expectations before the commencement of the initiated learning program (Kazu andDemiralp, 2016, Ornstern andHurgins, 2004). On this notion, teachers as active drivers in the implementation process were not inducted on how they should spearhead the initiative and this has provoked a negative attitude coupled with stiff resistance by the teachers (The Newsday, May, 2023, Juet et al, 2021). This is consistent with Gatawa (1992) whose view is that teachers need in-service training to keep them updated with major curriculum reforms.…”
Section: Discussion Of Findingsmentioning
confidence: 68%
See 3 more Smart Citations
“…Skilled workers would fully understand the expectations before the commencement of the initiated learning program (Kazu andDemiralp, 2016, Ornstern andHurgins, 2004). On this notion, teachers as active drivers in the implementation process were not inducted on how they should spearhead the initiative and this has provoked a negative attitude coupled with stiff resistance by the teachers (The Newsday, May, 2023, Juet et al, 2021). This is consistent with Gatawa (1992) whose view is that teachers need in-service training to keep them updated with major curriculum reforms.…”
Section: Discussion Of Findingsmentioning
confidence: 68%
“…Perilous findings of this study perceive that the teachers now shift all of their effort to CALA while ignoring to explain some concepts that are theoretical (Juet et al, 2021, OECD, 2019. The study also found out that the introduction of CALA has adversely impacted on the education of children because of irregularities that are beyond their coping strategies.…”
Section: Discussion Of Findingsmentioning
confidence: 84%
See 2 more Smart Citations
“…The other challenge that teachers highlighted was that of teaching both the practical and theoretical aspect of the content. Nyamudzodza, Mthombeni, Siziva, Sifile, and Manuere, (2021), Zhou (2021) state that the main feature of CALAs is the combination of understanding ideas and principles of the taught topics as well as doing practical work to enforce those concepts. This may imply that there is need for teachers to enhance both the theoretical and practical skills to enforce and apply CALAs.…”
Section: Teaching Both Practical and Theory Simultaneouslymentioning
confidence: 99%